Bridging the Gap: Enhancing Maritime Education for Shipping Management, Business, and Sustainability - Kwartama, Agung (Meteor STIP Marunda, 2024)
This research explores the alignment of maritime education with the dynamic demands of the maritime industry, focusing on shipping management, maritime business, financial systems, and sustainability. Through qualitative analysis, the study examines the perspectives of maritime industry professionals, lecturers, and recent graduates to evaluate the effectiveness of current educational frameworks. The findings reveal significant gaps in areas such as maritime finance, strategic business management, and sustainability practices. While foundational skills in port operations and logistics are well-covered, there is a critical need for enhanced focus on financial literacy, business strategies, and green shipping initiatives. Additionally, the integration of industry expertise into curriculum design and real-world applications is limited. The research suggests that stronger collaboration between educational institutions and the maritime industry, along with a more interdisciplinary approach to maritime education, can better prepare students for the evolving challenges of the global maritime sector. This study calls for a transformative shift in maritime education to equip future professionals with the necessary skills for sustainable and financially sound maritime practices.